Reutilización de lodos del proceso de anodizado de aluminio como materia prima para la elaboración de materiales para la construcción. - Razo Maya, Esteban Marcelo (2020)
The Aluminum Ecuadorian Corporation ("CEDAL") was founded in 1974 in Latacunga city and began production in 1976 as an aluminum extrusion company to supply the demand for architectural and structural profiles in the market. The anodizing process is an electrochemical process where the extruded profiles are entered into different chemical baths, resulting in wastewater and sludge where they are processed in the 'Effluent Plant' and the sludge residue that is the object understudy for the elaboration of construction materials. This research work aims to provide a sustainable alternative for the final disposal of the sludge generated in the aluminum anodizing process so, a baseline of the existing processes and the waste generated is presented where its quality, as well as sludge treatment, are verified. This study was proposed as the best option for the final disposal of sludge to work with methods that help reduce volumes of sludge generation and save the high costs of storage, transportation, and final disposal of waste. Consequently, it has been possible to produce construction materials using sludge as a raw material to make paving stones and concrete. Samples of paving stones were obtained in various proportions with both wet and dry mud, mixing proportions of 10, 25, 35, 50, and 75%, concerning other common materials such as rubble and cement. The optimal concentration of dry sludge is 25 and 35%, respectively, subjected to various mechanical tests established in the regulations NTE INEN 3040: 2016 and NTE INEN 0694: 2010 showing that they exceed the minimum resistance limit of 2.9 Mpa (29.58kg / cm 2). Therefore it was established that it is feasible to reuse the sludge in construction materials